Onset of Bronchodilation and Finger Tremor Induced by Salmeterol and Salbutamol in Asthmatic Patients - Jan Lötvall; Helen Lunde; Nils Svedmyr (Canadian Respiratory Journal)
Salmeterol is a beta-agonist with bronchodilator properties that last for at least 12 h after inhalation. However, the onset of action of salmeterol immediately after inhalation has not been sufficiently investigated. In the present study, the onset of action and tremor-inducing effect of two doses of inhaled salmeterol (50 and 100 µg) were compared with inhaled salbutamol (200 and 400 µg) and placebo. Lung function was measured using forced expiratory volume in 1 s (FEV), and tremor was measured using a linear accelerometer. With salbutamol there was rapid bronchodilation, both doses producing more than 15% improvement in mean FEV1 within 2 mins of inhalation. With salmeterol, on the other hand, significant bronchodilation was delayed until 7 mins versus placebo, and the full bronchodilation effect was not achieved until 60 mins after inhalation. There was a much more rapid onset of tremor with salbutamol (400 µg) than salmeterol. There was a much slower onset of bronchodilation with salmeterol than salbutamol. Therefore, salmeterol cannot be recommended to relieve acute symptoms.